Epidemiology of preeclampsia: update - Sánchez, Sixto E. (2015)
Preeclampsia is a complication of pregnancy characterized by inadequate placentation,resultant ischemia and failure of several maternal organs. Preeclampsia is one of the mostserious conditions in pregnancy and a leading cause of maternal and perinatal morbidity andmortality. Various risk factors and some protective factors have been reported associated topreeclampsia. Finally, women who develop preeclampsia during pregnancy are at higher riskof future diabetes mellitus, hypertension and cardiovascular complications. In this article anupdate on the epidemiology of preeclampsia is presented.Keywords: Preeclampsia, prevalence, risk factors, protective factors, complications, maternalmortality, perinatal mortality.